O ensino de produção textual: perspectivas historiográficas em dimensões linguísticas - Costa, Victor Matheus Victorino da (2015)
In this dissertation, we deal with the teaching of text production on High School, in the final of XX century and the beginning of XXI, more exactly between 1970 and 2000 decades. Starting wondering what are the theoretical and methodological notions that lay the foundation with text in high school classrooms in different historical moments, we seek to look closely to the text production propositions, aiming their teaching application. Our general objective is to evaluate the schoolwork found in curricular propositions and in textbooks. Our specific objectives are: to analyze and comprehend the theoretical positions followed, which guided to given didactic choices, and to analyze the linguistic and educational conception relating to the historical moment of each piece. To handle the proposed research, we are guided by Linguistic Historiography s principles and methodologies; referring to the text production study, we have Text Linguistics as basis. We procede, therefore, to the research and observation of São Paulo curricular propositions for Portuguese Language, fixing on the 70 and 90 decades, with the intention of understand and explain the point of view changes in the language teaching and the theoretical influences underlying these documents. Nationally, we comment the PCN (2000) and LDB (1971, 1996). Later, we go through the Text Linguistics theoretical developments and, finally we analyze the text production propositions in textbooks from the beginning of 70 and 2000 years. We could conclude, then, in each subtle change noted along the way of research, that in fact these developments of text studies and their refinement can contribute to the better educational development of students as a whole, and mainly their textual competence. In each new approaching expansion, we saw relationship more close to the texts em their social uses, exceeding the structural conception toward a functional one, merging, besides internal linguistic, interactive and social features